Evaluating the Macro Skills Proficiency of Out-of-School Youth and Adults - Marevic Jean Lutog (Universitas Galuh, 2026)
This study aimed to evaluate the macro skills of the Out of School Youth and Adults enrolled in the Alternative Learning System of the City of Mati, Davao Oriental. Included in the macro skills are listening, speaking, reading, writing, and viewing which are relevant to develop critical thinking, learning and effective communication. The OSYA are individuals who have not finished formal schooling due to a variety of reasons but are students of non-formal education. There are 100 respondents chosen by simple random sampling from the Mati North District and Mati Central District. Through a checklist, it was discovered that the OSYA have high levels of macro skills wherein listening is the highest while speaking is the lowest. This was based on their self-evaluation and analysis. Based from the results, it was concluded that listening is the most useful skill since it is relevant in understanding and participating in daily conversations. On the other hand, even though speaking has a high result, it still showed activities that are inconsistently executed. It is important that each macro skill should be developed to increase their competence in the language. Even though the study yielded high results, it is still significant to undergo additional investigation to further examine their macro skills. This research is also important to help the OSYA and ALS mobile teachers to strengthen their learning and teaching process